National Health Service: Responding to Current Challenges Through Necessary Transformations - Sakellarides, Constantino (2020)
After a decade experiencing clear difficulties, the Portuguese National Health Service needs a significant public investment for its development. This means more resources for the National Health Service, but also an increased capacity to manage its necessary transformation. Current health challenges differ significantly from those prevailing when the National Health Service was institutionalized, 40 years ago: (i) A significant increase in the prevalence of patients with multimorbidity has been observed; (ii)There is a need to delay and attenuate the expression of multimorbidity; (iii) In this context, a strong investment in integrating health care is of a paramount importance. The transformations that the National Health Service needs to respond to these challenges are very complex and demanding: (i) Effective local adaptive change management requires a very elaborate strategic, governance and government framework, which is yet to be developed; (ii) Collaborative architectures, processes and tools need to be promoted in order to induce and facilitate change in the Portuguese health system; (iii) Common understanding of current challenges and increased capabilities to deal with complex change processes may facilitate the implementation of effective strategic management in the National Health Service, focused on its more critical domains – financing, infrastructures and resource management, organizational development, policies for attracting and retaining health professional and cooperation with the social and private sectors. Such a transformation agenda is urgently needed.